1993
DOI: 10.1111/j.1365-2249.1993.tb07970.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of co-localizing cytokine and antibody producing cells in the extrafollicular area of human palatine tonsils

Abstract: SUMMARYIn r(7rf> experiments have documented the role of cytokines in the regulation of ihc human humoral immune response. Which cytokines are operative in vivo and in which lymphoid compartment interactions between cytokinc-producing T cells and antibody-forming B cells occur is still unclear. For that reason we studied human tonsils using immunohislochemical techniques. In tissue sections from tonsils in a resting stage after recurrent tonsillitis we observed cells producing IL-1 a and tumour neerosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…During the process of tonsillar immune response against foreign antigens, macrophages engulf the antigen and subsequently process and present it to CD4 + T-cells, which are then activated. Activation of CD4 + T-cells leads to the differentiation of antigen-specific B-cells, which finally differentiate into plasma cells and secrete Gd-IgA1 36,37 . Second, Cnm-positive S. mutans binds to the Fcγ receptors on macrophages by forming a complex with soluble CD89.…”
Section: Discussionmentioning
confidence: 99%
“…During the process of tonsillar immune response against foreign antigens, macrophages engulf the antigen and subsequently process and present it to CD4 + T-cells, which are then activated. Activation of CD4 + T-cells leads to the differentiation of antigen-specific B-cells, which finally differentiate into plasma cells and secrete Gd-IgA1 36,37 . Second, Cnm-positive S. mutans binds to the Fcγ receptors on macrophages by forming a complex with soluble CD89.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the comparative expression levels of IgA and IgG mRNA and protein in yak tonsils showed that the expression levels of IgG was very significantly higher than that of IgA in the same tonsil. These results were consistent with the distribution of two ASCs in the palatine tonsils of pigs (Horter et al, ; Li et al, ), horses (Kumar and Timoney, ) and humans (Hoefakker et al, ; Boyaka et al, ; Nave et al, ) but were significantly different from the results in Bactrian camels (Jia et al, ). Furthermore, as a secondary lymphoid organ, the tonsils mainly secreted large numbers of IgG and a few IgA to promote mucosal immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The activated CD4 + T-cells then activate B-cells to induce differentiation of antigen-specific B-cells in the follicles. B-cells finally differentiate into immunoglobulin-secreting plasma cells in the interfollicular area [ 19 ]. Thus, the interfollicular area is an important place where the antigen-specific T-cell activation and subsequent T-cell–B-cell interaction takes place.…”
Section: Discussionmentioning
confidence: 99%